1993
DOI: 10.1093/rheumatology/32.9.812
|View full text |Cite
|
Sign up to set email alerts
|

Home Exercises Are as Effective as Outpatient Hydrotherapy for Osteoarthritis of the Hip

Abstract: Hydrotherapy for OA of the hip has rarely been evaluated in controlled studies. Forty-seven patients with OA of the hip were followed for 18 weeks. Patients were randomly allocated either to a regimen of home exercises or to twice weekly hydrotherapy for 6 weeks in addition to home exercises. There was an improvement seen in both subjective and objective measures in both groups with treatment. There was no significant difference between the two groups. Response to treatment appeared independent of age, sex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 0 publications
0
43
0
4
Order By: Relevance
“…In contrast, two studies reported no significant reduction in pain following hydrotherapy in adults with arthritis. 41,42 Other studies suggest no additional reduction in pain with hydrotherapy than with immersion to the neck in heated water. 24,43 Nonetheless, these results have clinical relevance, and increased joint pain has been reported as the main reason for patients with rheumatoid arthritis stopping landbased exercises.…”
Section: Consequences Of Pathophysiology Of Jiamentioning
confidence: 99%
“…In contrast, two studies reported no significant reduction in pain following hydrotherapy in adults with arthritis. 41,42 Other studies suggest no additional reduction in pain with hydrotherapy than with immersion to the neck in heated water. 24,43 Nonetheless, these results have clinical relevance, and increased joint pain has been reported as the main reason for patients with rheumatoid arthritis stopping landbased exercises.…”
Section: Consequences Of Pathophysiology Of Jiamentioning
confidence: 99%
“…Patients had clinically and statistically significant improvements in self-perceptions of pain, stiffness, functional ability, and the distance walked in 6 minutes. Green et al 9 found that simple home exercises were beneficial in patients with osteoarthritis of the hip in improving range of motion and strength. Hoeksma et al 13 found that manual therapy, including manipulation and stretching techniques, had better outcomes than exercise therapy in improving pain, stiffness, range of motion, and function in patients with hip osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies report mixed results regarding the physical effects of aquatic exercise on persons with arthritis (Hansen, Hansen, Langgaard, & Rasmussen, 1993;Green, McKenna, Redfem, & Chamberlain, 1993).…”
Section: Studies Of Physical Effectsmentioning
confidence: 99%
“…The authors state that outcome measures regarding quality of life, depression, and anxiety would have been better indicators to detect general satisfaction with exercise training (Hansen et al, 1993). Green, McKenna, Redfem, and Chamberlain (1993) concluded that home exercises are as effective as outpatient hydrotherapy for persons with hip OA. They examined objective measures (ROM, strength), subjective measures (pain, need for medications), and functional measures (ability to rise from chair, time and number of steps taken to walk a fixed distance, and time taken to walk up and down a staircase).…”
Section: Studies Of Physical Effectsmentioning
confidence: 99%
See 1 more Smart Citation